EXPRESSION ANALYSIS OF MIR-1 AND MIR-133 IN THREE DEVELOPMENTAL STAGES OF GOAT SKELETAL MUSCLE - Yinghui Ling; Lijuan Wang; JianpingDing; Lisheng Wang; Yunhai Zhang; Xiaorong Zhang (Journal of Animal and Plant Sciences, 2015)
MiR-1 and miR-133 are evolutionary conserved in most animal species, from drosophila to human, and have been confirmed to take an important role for skeletal muscle development in mice and pigs. In this study, the function of miR-1 and miR-133 was detected through analysis the expression pattern of the two miRNAs and their predicted target genes in three developmental stages of goat skeletal muscle. HDAC4 and SRF, which were the target genes of miR-1 and miR-133 family, respectively, were predicted using MiRanda and Target Scan 6.2 software. Then the expression profiles of miR-1, miR-133, HDAC4 and SRF in 10 normal goat tissues (heart, liver, spleen, lung, kidney, small intestine, fat, longissimusdorsi muscles, pectoral muscles and crural muscles) from three stages (newborn, three months, eighteen months) of Anhui White goat were characterized by real-time RT-PCR. The expression of miR-1 and miR-133 were varied among different tissues, with most abundant in heart and skeletal muscles (longissimusdori muscles, pectoral muscles and crural muscles) in Anhui white goats, while there were the least expression in other tissues. However, the expression levels of HDAC4 and SRF were on the contrary. The results suggested that miR-1 and miR-133 may enhance myoblast proliferation and differentiation by repressing their predicated target genes, thus affecting skeletal muscle growth and development. This study will be a useful reference for further studies about miR-1 and miR-133 for their role in the regulation in animal growth and development processes.
Keywords: miR-1 and miR-133; goat; target gene; growth and development; expression profiles